Crowdsourcing for Speech Processing: Applications to Data Collection, Transcription and Assessment - Eskenazi, Maxine; Levow, Gina-Anne; Meng, Helen; Parent, Gabriel; Suendermann, David (Wiley, 2013)
The concept of crowdsourcing is based on the observation that if a crowd of non-experts is asked an opinion, the aggregation of their individual opinions will be very close to the true value. Tasks such as collecting speech, labelling it, assessing systems and carrying out studies on the speech data are natural candidates for crowdsourcing. This book is a detailed and hands-on comprehensive reference for those who want to use crowdsourcing for speech applications. From the reader who has already used crowdsourcing and wants to refine their methods to the novice who has never used this technique before; this book will provide a practical introduction to crowdsourcing as a means of rapidly processing speech data with contributions from leading researchers in the field. Informs readers about how to collect and label speech using crowdsourcing; how to assess speech applications and run perception studies using crowdsourcing. Explains to readers about how to choose crowdsourcing platforms. Considers the ethical and legal implications of performing crowdsourcing for speech processing. Includes numerous real-life examples of how to implement crowdsourcing for various types of speech processing. Offers several options for each type of task enabling readers to choose which option best fits their individual needs. Provides an extensive overview of the literature on crowdsourcing for speech processing.